Fumigant toxicity and persistence of essential oils from asafetida, geranium, and walnut on adults of Rhyzopertha dominica (Col.: Bostrichidae). (1st October 2016) - Bahrami, Rahim; Kocheili, Farhan; Ziaee, Masumeh
Abstract: Fumigant toxicity and persistence of asafetida, geranium, and walnut essential oils were investigated against adults of Rhyzopertha dominica (F.). The experiments were conducted at 28 ± 2 °C, 65 ± 5% RH in continuous darkness. Fumigant toxicity of the essential oils was higher in the empty glass vials than when wheat was treated with the oils. Asafetida oil was more toxic than the two other tested plant species. The essential oil of asafetida was persisted 7 days with 65.71 h half-life time; while the half-life time of geranium and walnut essential oils was 43.39 and 49.37 h, respectively. The present study suggests that asafetida oil may be potential use as stored products protectant.